2014
DOI: 10.1002/ijc.28759
|View full text |Cite
|
Sign up to set email alerts
|

PTPRG inhibition by DNA methylation and cooperation with RAS gene activation in childhood acute lymphoblastic leukemia

Abstract: While the cytogenetic and genetic characteristics of childhood acute lymphoblastic leukemias (ALL) are well studied, less clearly understood are the contributing epigenetic mechanisms that influence the leukemia phenotype. Our previous studies and others identified gene mutation (RAS) and DNA methylation (FHIT) to be associated with the most common cytogenetic subgroup of childhood ALL, high hyperdiploidy (having 5 more chromosomes). We screened DNA methylation profiles, using a genome-wide high dimension plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…28,29 Thus, additional cooperating factors must influence survival of these low-level mutated clones during treatment and contribute to Ras pathway-mutated leukemia progression and relapse. 30 Although transgenic models suggest that oncogenic Ras can initiate leukemia and may be a primary event (reviewed in Ward et al 31 ), we show that this is a common secondary genetic event during leukemogenesis that may or may not confer a survival advantage during ALL therapy.…”
Section: Discussionmentioning
confidence: 58%
“…28,29 Thus, additional cooperating factors must influence survival of these low-level mutated clones during treatment and contribute to Ras pathway-mutated leukemia progression and relapse. 30 Although transgenic models suggest that oncogenic Ras can initiate leukemia and may be a primary event (reviewed in Ward et al 31 ), we show that this is a common secondary genetic event during leukemogenesis that may or may not confer a survival advantage during ALL therapy.…”
Section: Discussionmentioning
confidence: 58%
“…PTPRG expression has been shown to be down-regulated by RAS activation, while its up-regulation has been observed in hypo-methylation condition in in childhood acute lymphoblastic leukemia (ALL) [48]. Finally, PTPRG methylation has also been reported in solid cancer [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Promoter methylation is also an important mechanism for PTPR inactivation in cancer. PTPRG is hypermethylated in multiple cancers including breast cancer [36] , gastric cancer [37] , nasopharyngeal carcinoma [38] , Lynch syndrome CRC [39] , childhood acute lymphoblastic leukemia [40] , and cutaneous T-cell lymphoma [41] . PTPRG expression is negatively correlated with methylation, and when treated with methylation-suppressive agents like 5-aza-2′-deoxycytidine, PTPRG expression can be recovered [37] , [41] .…”
Section: Genetic and Epigenetic Alterations Of Ptprsmentioning
confidence: 99%
“…PTPRG expression is negatively correlated with methylation, and when treated with methylation-suppressive agents like 5-aza-2′-deoxycytidine, PTPRG expression can be recovered [37] , [41] . A study of childhood acute lymphoblastic leukemia suggested that PTPRG methylation is induced by Ras mutations [40] .…”
Section: Genetic and Epigenetic Alterations Of Ptprsmentioning
confidence: 99%